Analisa Animasi Tokoh Hero Mobile Legends Kadita yang Terinspirasi dari Legenda Nyi Roro Kidul - Hutomo Setia Budi; Shienny Megawati (JURNAL RUPA, 2022)
In 2018, Mobile Legends launched animation of a hero Kadita which was inspired by the legend of Nyi Roro Kidul. Kadita’s design was adapted to popular culture, with a traditional Indonesian (Javanese-Balinese) aesthetic. In Kadita’s introduction animation, there were visual elements inspired by Indonesian culture with traditional background music. This study aimed to examine whether the visual elements of Indonesian culture were displayed correctly, alongside with the response of millennial and z generations toward the animation. The research was conducted with a qualitative approach through interviews with experts on Indonesian traditional culture and through focus group discussions with millennials and z generations to find out their responses toward traditional Indonesian culture displayed in popular media. Primary data collection was carried out through a literature review on traditional culture and popular media. The conclusion of this research, the animation of “Kadita the Ocean Goddess” succeeded in adapting traditional Indonesian elements in popular media. The results of the FGD showed that the target audience responded positively to the traditional culture displayed in popular media. This research can be used as a basis for thinking and designing strategies in an effort to introduce Indonesian traditional culture to the younger generation using popular media. Keywordsanimation, adaptation, character, folklore, pop culture, promotion, traditional culture, visualization, wayang, Z generation